Linguistic approaches to Portuguese as an additional language - Molsing, Karina Veronica; Perna, Cristina Becker Lopes; Ibaños, Ana Maria T. (Ana Maria Tramunt) (Issues in Hispanic and Lusophone linguistics ;, 2020)
"This book includes a selection of theoretical and practical accounts of the acquisition of Portuguese from a broad range of linguistic perspectives. This collection is particularly appealing in the broad academic sphere of language acquisition due to the fact that there has yet to be one entirely dedicated to Portuguese as an Additional Language (PAL). This volume showcases the breadth of research being carried out on topics ranging from the acquisition of aspects from the main language modules (syntax, morphology, semantics, phonology, and pragmatics) to applied perspectives involving corpus-based approaches and experimental methodologies. Moreover, we present studies addressing a variety of learning contexts and learner types. The target audience includes researching scholars with a background in second language acquisition studies interested in learning more about the acquisition of Portuguese as an Additional Language from linguistic perspectives"--